Criteria and indicators toolbox series, no. 1 - 9 (Center for International Forestry Research, 1999)
The CIFOR C&I Toolbox series is designed to help people make assessments of management in particular production forests where people live and work in and around the forests. The assessment include aspects relating to management, environment and human well-being. The toolbox has developed a generic set of principles, criteria and indicators, related method and samples.